PENGARUH RASIO PERTUMBUHAN PENDAPATAN TERHADAP KINERJA KEUANGAN DAERAH KOTA MALANG - Sadi Putra, Ari Kusumayanti (Jurnal Riset Mahasiswa Akuntansi, 2014)
Regional autonomy (decentralization) is a regional authority to regulate and manage the interests of society at its own initiative based on community aspirations and according to laws and regulations. One aspect of local government that must be regulated carefully is the financial management area. To analyze the performance of local governments in managing local finances can be done with the financial ratio analysis. The financial ratios used include: the ratio of independence and growth ratio revenue. This study aimed to examine the effect of the local original revenue (PAD) on the financial performance in Malang City. This type of research is descriptive quantitative replication model. Data collection techniques in this study is documentation and library research. Variables used is independen as growth ratio and dependen as financial performance. The analysis technique used is linear analysis. The results showed that the local original revenue (PAD) significantlyinfluence of the financial performance.